Analyzing Peace Journalism in Cyber Media: Coverage of Ethno-Religious Conflicts in Indonesia - Ahmad Junaidi (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This study focuses on the reporting dynamics of the Sunda Wiwitan indigenous community’s land conflicts by scrutinizing the role of journalists and sources in shaping media narratives and public discourse. A historical backdrop is provided, detailing communal conflicts after Suharto’s fall and emphasizing the media’s influential role in potentially exacerbating or mitigating conflicts. The research method integrates quantitative and qualitative analyses, including a content analysis of 110 news articles and interviews with journalists and community members to explore the application of peace journalism principles. The findings reveal the predominant use of hard news, with a nuanced implementation of peace-, truth-, community-, and solution-oriented principles. The analysis indicated balanced coverage between the physical and non-physical impacts of conflict, a trend towards opinionated rather than factual reporting, and a strong representation of the indigenous community’s voice. The study recommends enhancing balanced reporting, promoting in-depth analysis, strengthening solution-focused journalism, providing peace journalism training, and encouraging diverse perspectives on conflict coverage. These measures aim to improve journalism’s role in fostering peace and understanding societal conflict.